INDONESIA'S DEMOCRACY AND CONSTITUTION: REFLECTING HUMAN RIGHTS BASED ON PANCASILA - Ria Wierma Putri; Febryani Sabatira; Orima Melati Davey; Muhammad Febriyan Saputra; Rudi Natamiharja (Universitas Internasional Batam, 2022)
Pancasila democracy is a democracy system applied in Indonesia to run the government based on the 1945 Constitution. The 1945 Constitution is positioned as the state constitution and is a concrete crystallization of Pancasila’s values. The constitution, which is the highest source of law in Indonesia, is very important in the Pancasila democratic system. The relationship between the Democracy, Human Rights, and Pancasila is very concord. Pancasila is the ideology of the Indonesian state, the basis of the state, and the foundation of the state philosophy. The relationship is contained in the values of Pancasila. These values highly uphold human rights which is seen from the second value of Pancasila, “fair and civilized humanity”. The relationship between democracy with human rights and Pancasila is that democracy is a system used in Indonesia to realize Pancasila’s values while still based on human rights in its implementation. Then, Pancasila must always remain the basis of the state’s philosophy because Pancasila is the result of the nation founders’ consensus agreement. Pancasila values are not owned by other countries in the world and has become the Indonesian nation’s identity. Pancasila is supreme because it is the core foundation in uniting the diverse Indonesian nation. In addition, ideals of law do not only function as a regulatory benchmark to test whether a positive law is fair, but it also serves as a constitutive ground. Therefore, laws will lose it definition without the existence of ideals of law.